Assessment of sympathetic sudomotor function in amyotrophic lateral sclerosis with electrochemical skin conductance. Issue 9 (September 2021) - Oliveira Santos, Miguel; Castro, Isabel; Castro, José; Gromicho, Marta; de Carvalho, Mamede
Highlights: Electrochemical skin conductance is a new method to quantify sudomotor function. ALS patients had a decreased palmar and plantar sudomotor function. Abnormal sudomotor function is part of the ALS disease spectrum. Abstract: Objective: Amyotrophic lateral sclerosis (ALS) is now recognized as a multisystem neurodegenerative disorder, comprising autonomic dysfunction. We aimed to assess sudomotor function in ALS by measuring the electrochemical skin conductance (ESC). Methods: Thirty-one ALS patients [median age of 62 years (1st-3rd interquartile range – IQR, 56–72), male 71%] were prospectively compared with 29 healthy controls, matched for age and sex. We analysed ESC results from hands and feet, bilaterally. Results: A total of 120 ESC recordings were obtained. Hands and feet ESC measurements were significantly lower in patients compared with controls [64 μS (1st-3rd IQR, 57–58) versus 78 μS (1st-3rd IQR, 70.5–84), p  < 0.001 and 76 μS (1st-3rd IQR, 68–83) versus 81 μS (1st-3rd IQR, 78–86), p  = 0.008, respectively]. In ALS group, no differences were observed between spinal and bulbar-onset forms for hands and feet results ( p  > 0.05). Hands and feet ESC measurements did not correlate also with disease duration, total ALSFRS-R scale, or ALSFRS-R progression rate (all p  > 0.05). Conclusion: ESC is a non-invasive, fast and quantitative method suitable for assessing sudomotor function. ALS patients revealed a decreased function in upper and lower extremities. Significance: Sudomotor dysfunction is part of the ALS manifestations.